Protecting food security in the face of tariffs and trade wars - Teng, Paul (2025)
The uncertainty caused by tariffs and trade disputes affects food security. Increases in geopolitical tensions will undermine the best plans to maintain global supply chains, encouraging countries to develop alternative ones. Consumers in Southeast Asia, even though far from the geographic areas of dispute, will ultimately suffer from interruptions in food availability and price hikes. National strategies to ensure food security are needed.